Helicobacter pylori eradication in complicated peptic ulcer: Beneficial in most? - Subair Mohsina; Anitha Muthusami; Gomathi Shankar; Sathasivam Sureshkumar; Vikram Kate (International Journal of Advanced Medical and Health Research, 2016)
Helicobacter pylori eradication therapy has a role in minimizing the complications of peptic ulcer disease, namely, bleeding, perforation, and obstruction. However, the precise role of H. pylori eradication therapy in the complicated ulcers remains inconclusive, especially in perforation and gastric outlet obstruction. The prevalence of H. pylori in peptic ulcer bleeding patients has been widely underestimated owing to the differences in diagnostic tests and patient characteristics, and hence, it is recommended that an initial negative test should be followed up by a delayed repeat testing to rule out false negativity. It is well established now that eradication of H. pylori in patients with bleeding ulcers reduces rebleeding and ulcer recurrence. Multiple studies have attributed high recurrence rates of duodenal ulcer following simple closure to a high prevalence of H. pylori infection. Eradication therapy decreases the recurrence rate of perforated ulcers, thus justifying the role of H. pylori eradication therapy following the primary surgical management of perforated ulcers. The role of H. pylori in duodenal ulcer with gastric outlet obstruction is yet to be evaluated clearly. There are some reports of resolution of gastric outlet obstruction following therapy for H. pylori, obviating the need for surgery. Clarithromycin-containing regimens are recommended as first-line in areas of low resistance, whereas bismuth-containing quadruple therapy is the first-line empirical treatment in areas of high clarithromycin resistance. Treatment of H. pylori is beneficial in most of the patients with complicated peptic ulcer disease, especially in reducing recurrence of ulcer with or without complications.